Development of di-methacrylate quaternary ammonium monomers with antibacterial activity. (15th July 2021) - Fanfoni, Lidia; Marsich, Eleonora; Turco, Gianluca; Breschi, Lorenzo; Cadenaro, Milena
Abstract: Nine antibacterial di-methacrylate monomers based on bis-quaternary ammonium salts (bis-QAMs) were synthesized and structurally characterized. The biological activity of the bis-QAMs was tested in terms of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) on different bacterial strains achieving promising results and, in most cases, a complete bactericidal effect using a bis-QAM concentration lower than 1 mg/mL. Two of the structures showed comparable and superior activity against S. mutans than the commercial monomer 12-methacryloyloxydodecyl pyridinium bromide (MDBP). All the bis-QAMs here described were able to inhibit S. mutans biofilm formation at a concentration equal to the MIC value. From the analysis of the obtained data, some correlation regarding the structure and the antibacterial activity of the bis-QAMs could be drawn: a flexible alkyl C12 spacer between the two quaternary ammonium moieties increased the monomer antibacterial effect in comparison to the aromatic ones; the equilibrium between hydrophobic and hydrophilic moieties was directly correlated to the bactericidal range of action; the increase of the steric hindrance of the ammonium side groups might be both advantageous or disadvantageous to the antibacterial efficacy depending on the whole monomer chemical structure. Even though the possible correlation between the monomer structures and their bacteriostatic or bactericidal effect is under investigation, the monomers exhibited low cytotoxicity on human dental pulp stem cells, confirming their promising potential in the dental materials' field. Statement of significance: The use of dental resins with antibacterial monomers might prevent the formation of secondary caries at the restoration margins. For this purpose, a series of di-methacrylate bis-quaternary ammonium monomers (QAMs) was developed. Unlike antibacterial mono-methacrylate monomers already described in the literature, the synthesized di-methacrylate monomers have the potential of acting as cross-linkers stabilizing the polymeric network and bear two quaternary ammonium groups that increase their antibacterial ability. The QAMs exert bactericidal activity on both Gram(+) and Gram(−) bacterial strains maintaining at the same time good biocompatibility with the oral environment. Some structural elements of the monomers were clearly related to high antibacterial properties, and this can help design new active structures and better understand their mechanism of action. Graphical abstract: Image, graphical abstract